Structure-Function Analysis of the Curli Accessory Protein CsgE Defines Surfaces Essential for Coordinating Amyloid Fiber Formation - Roger D. Klein; Qin Shu; Zachary T. Cusumano; Kanna Nagamatsu; Nathaniel C. Gualberto; Aaron J. L. Lynch; Chao Wu; Wenjie Wang; Neha Jain; Jerome S. Pinkner; Gaya K. Amarasinghe; Scott J. Hultgren; et al. (mBio, 2018)
ABSTRACT Curli amyloid fibers are produced as part of the extracellular biofilm matrix and are composed primarily of the major structural subunit CsgA. The CsgE chaperone facilitates the secretion of CsgA through CsgG by forming a cap at the base of the nonameric CsgG outer membrane pore. We elucidated a series of finely tuned nonpolar and charge-charge interactions that facilitate the oligomerization of CsgE and its ability to transport unfolded CsgA to CsgG for translocation. CsgE oligomerization in vitro is temperature dependent and is disrupted by mutations in the W48 and F79 residues. Using nuclear magnetic resonance (NMR), we identified two regions of CsgE involved in the CsgE-CsgA interaction: a head comprising a positively charged patch centered around R47 and a stem comprising a negatively charged patch containing E31 and E85. Negatively charged residues in the intrinsically disordered N- and C-terminal “tails” were not implicated in this interaction. Head and stem residues were mutated and interrogated using in vivo measurements of curli production and in vitro amyloid polymerization assays. The R47 head residue of CsgE is required for stabilization of CsgA- and CsgE-mediated curli fiber formation. Mutation of the E31 and E85 stem residues to positively charged side chains decreased CsgE-mediated curli fiber formation but increased CsgE-mediated stabilization of CsgA. No single-amino-acid substitutions in the head, stem, or tail regions affected the ability of CsgE to cap the CsgG pore as determined by a bile salt sensitivity assay. These mechanistic insights into the directed assembly of functional amyloids in extracellular biofilms elucidate possible targets for biofilm-associated bacterial infections. IMPORTANCE Curli represent a class of functional amyloid fibers produced by Escherichia coli and other Gram-negative bacteria that serve as protein scaffolds in the extracellular biofilm matrix. Despite the lack of sequence conservation among different amyloidogenic proteins, the structural and biophysical properties of functional amyloids such as curli closely resemble those of amyloids associated with several common neurodegenerative diseases. These parallels are underscored by the observation that certain proteins and chemicals can prevent amyloid formation by the major curli subunit CsgA and by alpha-synuclein, the amyloid-forming protein found in Lewy bodies during Parkinson’s disease. CsgA subunits are targeted to the CsgG outer membrane pore by CsgE prior to secretion and assembly into fibers. Here, we use biophysical, biochemical, and genetic approaches to elucidate a mechanistic understanding of CsgE function in curli biogenesis.